Новый вид рода Hygroplitis (Hymenoptera, Braconidae) с Сахалина - Котенко, А.Г. (Вестник зоологии, 1993)
H. basarukini sp. n. is described from Northern Sakhalin. From closest european H. russata difiers by the black colour of 1—3 abdominal tergites, wider pterostigma, narrower 1st abdominal tergite ect.; from North-Americal H. melligastra — by shorter preapical antennal segment. Type material is deposited in the Institute of Zoology, Ukrainian Academy of Sciences (Kiev).